Operationalization of print's situation analysis model in general teacher education curriculum and inclusive education - Sawi, Katherine Jane I.; Fajardo, Amelia C.; Muega, Maricris B. Acido; Manzano, Virgilio U.; Tantengco, Myra Trinidad Timtiman (Quezon City College of Education, University of the Philippines Diliman, 2020)
The study determines the degree of applicability of Print's situation analysis in the Philippine setting by examining the general situation and relative education. To operationalized Print's model, semi-structured interview, survey questionnaires, and observation were used. Interview questions were made based on Print's situation analysis framework. The data were collected from 55 participants in Manadaluyong City, Quezon City and Benito Soliven. The data were analyzed using concepts, constructs and theme (CCT) analysis, factor analysis, principal component analysis and Pearson correlation. It was found that Print's model is applicable in Philippine setting. The model is useful in providing an easy to follow, straightforward, and logical process in analyzing the context because it focuses on one element at a time. Data gathering methods that Print recommended were effective in collecting relevant information about the problem and appropriate factors in general education curriculum and inclusion. Analysis of data on the appropriate factors led to recommendation that can serve as a basis for curricular goals. Guidelines in creating interview questions, criteria for selection of survey questionnaires and selection of participants were made. There are additional external and internal factors that were added to those listed by Print School community support, inclusive culture, government support, collaboration, students' preparedness and parental support are additional factors that have been identified by operationalizing Print's model.
Thesis (Master of Arts in Education - Curriculum Studies)--University of the Philippines, Diliman
Includes bibliographical references (pages 155-160)
Keywords: Teachers -- Training of -- Philippines